Multi-proxy stalagmite records from northern California reveal dynamic patterns of regional hydroclimate over the last glacial cycle. (1st August 2020) - Oster, Jessica L.; Weisman, Isabelle E.; Sharp, Warren D.
Abstract: Despite its importance for California's water resources, little is known about how precipitation has varied in far northern California beyond the historical record. We present a new, multi-proxy paleoclimate record derived from two coeval stalagmites from Lake Shasta Caverns (LSC), California that covers the end of Marine Isotope Stage 3 through Heinrich Stadial 1 (∼35, 000 to 14, 000 years BP). At 40.8°N, LSC is situated within the transition zone between regions in the northwestern and southwestern United States that demonstrate different precipitation responses to both modern and paleoclimatic drivers. Stable isotope and trace element proxies from LSC stalagmites indicate the region experienced wet conditions during interstadials (warm periods) associated with Dansgaard-Oeschger cycles, similar to proxy records from southern Oregon and the northern Great Basin, but in contrast to records from the desert southwest. Similar to the northern Cascades and Rocky Mountains, LSC was drier during the Last Glacial Maximum. However, proxies indicate increased rainfall throughout Heinrich Stadial 1, similar to the Great Basin and southwest. Thus, the LSC record demonstrates the non-stationarity of the transition zone location and illustrates a complex pattern of precipitation response to global climate change in the western United States. Covariation of speleothem δ 18 O, an indicator of moisture source, with δ 13 C and trace elements, indicators of moisture amount, suggest a higher proportion of Central Pacific precipitation during the Last Glacial Maximum, despite the enhanced aridity. In contrast, periods characterized by increased precipitation amounts, such as early Heinrich 1, are associated with enhanced moisture from the Northern Pacific. Highlights: Multiproxy, replicated stalagmite paleoclimate record from Northern California. Location of transition between dry and wet regions in western US in response to global paleoclimate events varies in time. Increase in Central Pacific-sourced precipitation not always associated with overall increased rainfall in northern California.